(untitled) (Quinto Sol, 2017)
An open dialogue and negotiations environment allowed for consolidation of the central government in the provinces. Also, local elites obtained benefits for their own provinces, supported by the engagement capabilities of the intermediaries involved. The 1870 decade in Tucuman is characterized by two aspects. On one hand, the successful modernization of the sugar industry fully supported by the national government, and on the other, the heavy impact of the international financial crisis upon national economy. This article analyzes the structure of public spending in Tucuman with special attention to the distribution of subsidies and grants from the national government to the provinces in a crisis situation. Also it studies the preferential policies towards some states and not in favor of others due to the discretional management of national income. We also examine unorthodox channels through which subsidies and/or monetary aid were managed that the provincial state continued to receive when the crisis forced the national government to suppress them.